2006
DOI: 10.1192/pb.30.7.269
|View full text |Cite
|
Sign up to set email alerts
|

Service innovations: redesigning a community mental health team

Abstract: Aims and MethodWe describe the redesign of a community mental health team in Lanarkshire (the focused intervention team for Bellshill). Their remit is to provide focused, time-limited therapeutic intervention for patients with mild-to-moderate mental health problems.ResultsThe redesign involved a closer working relationship with the psychiatrist, establishing a concurrent community psychiatric nurse/ psychiatric clinic, recategorisation of ‘soon’ and routine referrals to the team, opt-in letters and the introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Patients who require more specialist mental health services than the GP can provide are referred to a Community Mental Health Team (CMHT). However it has been identified that CMHTs are not adequately able to respond to current demands and are faced with more referrals than they are able to manage, resulting in waiting lists to access the service and large numbers of patients within their caseloads (Shajahn, Forde, McIntosh, Moffat, & Munogee, 2006). A significant downfall of CMHTs is that they cannot provide adequate crisis intervention services where support is available to patients outside of office working hours (Mental Health Council of Australia, 2005).…”
Section: Who Provides Mental Health Care In the Community?mentioning
confidence: 96%
“…Patients who require more specialist mental health services than the GP can provide are referred to a Community Mental Health Team (CMHT). However it has been identified that CMHTs are not adequately able to respond to current demands and are faced with more referrals than they are able to manage, resulting in waiting lists to access the service and large numbers of patients within their caseloads (Shajahn, Forde, McIntosh, Moffat, & Munogee, 2006). A significant downfall of CMHTs is that they cannot provide adequate crisis intervention services where support is available to patients outside of office working hours (Mental Health Council of Australia, 2005).…”
Section: Who Provides Mental Health Care In the Community?mentioning
confidence: 96%
“…Several papers referred to the weekly MDT meeting as the "referral meeting" or the "allocation meeting" (Simpson and de Silva, 2003;Mitchell and Patience, 2002;King, 2001;Mohan et al, 2004). Seven papers mentioned teams having discussions about which practitioner would be most suitable to work with a given patient (Lankshear, 2003;McCrae et al, 2008;Simpson, 2007, Burns, 2006Ingram and Tacchi, 2004;Shajahan et al, 2006;Social Services Inspectorate, 2001). In theory, this decision was to be made by finding the most suitable match between a specific case and the expertise of a particular professional.…”
Section: Thematic Synthesismentioning
confidence: 99%